Research on Aircraft/Engine Integrated Method of Civil Aircraft Products Development Oriented to System Engineering. Issue 1 (October 2020) - Jinhai, Yu; Jilei, Fu; Yi, Lu; Shan, Fu; Dan, Huang; Xin-Ai, Zhang
Abstract: This research proposes an aircraft/engine integrated design system construction method for civil aircraft based on system engineering oriented to large civil aircraft airworthiness certification. The aircraft/engine integrated design system of civil aircraft based on the "mapping model" highlights the logical completeness of the development evidence. This research contains two types of core design evidence: 1) design data of aircraft/engine integrated system; 2) aircraft/engine integrated system confirming and verifying data. The mapping model corresponds to the constraints of airworthiness regulations on the aircraft/engine integrated system design in three aspects: requirements analysis and confirmation, functional design, and design execution and verification, which promotes design data and airworthiness compliance evidence build in parallel.